Práticas de gestão econômica e financeira adotadas por redes de empresas estabelecidas no estado do Rio Grande do Sul - Menegotto, Margarete Luisa Arbugeri (Universidade do Vale do Rio dos Sinos, 2010)
The objective of the present study was to identify which practices of economic and financial management are used by business networks in Rio Grande do Sul. The usage of practices of the economic and financial management allows the evaluation of the actions as well as the obtainment of needed information for decision-making. Structured interviews were used to obtain the data about the usage of these practices.The interviews were applied to 21 business networks in Rio Grande do Sul, which composed the sample of this research. The data collection instrument took into account the aspects referring to the reasons of business network formation; different forms on choosing the associates; structure and formalization of the networks; practices of economic and financial management; corporate governance; general characteristics of networks and respondents’ profile. The data collected was submitted to the descriptive analysis where middle ranking and the percentage of usage were calculated based on the answers obtained on the Likert scale. The factorial analysis was performed in order to reduce the number of variables as well as to form factors which underwent multiple bivariate correlations in order to examine the relationship among them. Based on these analyses, it was possible to verify that business networks are established to increase competitiveness, reduce costs and achieve partnerships. It was found that 76% of the sample is composed of associations, and that the networks that have transaction value exceeding R$ 10 million per year used the practices of economic and financial management with greater intensity than those with less volume. With respectto the practices of economic and financial management, it was found that the price quotation with potential suppliers and cash flow are most used by the sample. The results suggest that, when it comes to economic and financial management of networks, the focus is on short term, since the first three positions have this statement in the rankings classification.
Keywords: Alianças estratégicas; Redes de empresas; Governança; Gestão econômica e financeira; Redução de custos; Strategic alliances; Business network; Governance; Economic and financial management; Cost reduction; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis